2001
DOI: 10.1007/s002460010238
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Insufficiency and Renal Replacement Therapy After Pediatric Cardiopulmonary Bypass Surgery

Abstract: The aim of the study was to investigate renal function and renal replacement therapy after cardiopulmonary bypass surgery in children. Patient characteristics (sex, age, diagnosis), operation type, and death were listed. The study was performed retrospectively using serum creatinine level before, and peak values after, cardiopulmonary bypass surgery for assessment of renal function. Of the children on renal replacement therapy, indication, efficacy, and complications were recorded. In a 5-year period, 1075 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 12 publications
4
57
0
9
Order By: Relevance
“…[1][2][3] Continuous veno-venous hemodiafiltration (CVVH) is used as one of the modalities of CRRT in pediatric intensive care units. ARF is still a frequent complication following extensive pediatric cardiac surgery due to low cardiac output, massive hemolysis and high fluid overload.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Continuous veno-venous hemodiafiltration (CVVH) is used as one of the modalities of CRRT in pediatric intensive care units. ARF is still a frequent complication following extensive pediatric cardiac surgery due to low cardiac output, massive hemolysis and high fluid overload.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Peritoneal dialysis is the first-line RRT modality which is relatively easy to employ, effective, and has a low complication rate to be used for ARF in these patients. [1,4,13,14] Several studies have attempted to identify the risk factors of ARF requiring RRT in pediatric patients undergoing congenital cardiac surgery. [2,7,14] In consistent with previous studies, [15][16][17] patients who showed recovery of renal function following PD with associated lower CPB and CC times, RACHS-1 category and inotrope scores, BUN and SCr values before PD and a lower time interval between surgery and PD had lower mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1,19] In addition, the incidence of postoperative ARF can be as high as 42% with an incidence of 1 to 17% for dialysis and a mortality rate of 20 to 100%. [12,15,16,19,20] The incidence of ARF, which required PD and mortality rate following congenital cardiac surgery in our study population, were 7.9% and 72.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations